New Weather channel “Internet” - Sánchez Calero, María Luisa; Pardina Horno, Jorge (Estudios sobre el Mensaje Periodístico, 2012)
Analyse trends and positioning that acquires the weather in digital press and specific portals has undergone a comprehensive and extensive research. But this single article shows a part of it where highlighting the characteristics of nine weather portals with strong presence in the Spanish webs of meteorology where aspects have been analysed as: language and vocabulary used, the sources consulted, the organization of the contents, search, graphic material, alert systems, the communicating systems and user interaction possibilities. It has required methodologically designing a questionnaire and send 400 surveys aimed to capture the profile of users consulting this information on the websites. Addition to analysing 30 websites and public and private Spanish portals linked to sports areas or leisure there a section highlighted on the meteorological information. And finally, the identification and study of 9 portals specific meteorological information were identified as referenced in the previous study of the related web sites with aspects of leisure, sports and outdoor activities.